Peer Effects on Engagement and Disengagement: Differential Contributions From Friends, Popular Peers, and the Entire Class - Steenberghs, Nina; Lavrijsen, Jeroen; Soenens, Bart; Verschueren, Karine (Frontiers in Psychology, 2021)
School engagement and disengagement are important predictors of school success that are grounded in the social context of the classroom. This study used multilevel analysis to examine the contributions of the descriptive norms of friends, popular students and classmates regarding engagement and disengagement to the development of students’ own behavioral and emotional engagement and disengagement among Flemish 7th graders (N = 3,409). Moderating effects of students’ self-esteem and cognitive ability were examined. The results showed effects from friends’ and classmates’ (dis)engagement on all dimensions of (dis)engagement. Popular students’ engagement only affected individual student’s behavioral disengagement and emotional engagement. Self-esteem and high cognitive ability did not make students more or less susceptible to peer effects.